Políticas públicas em saúde bilíngue para surdos: percursos, percalços e o cotidiano - Trevisan, Sueli Fioramonte (Universidade Federal de São Carlos, 2023)
According to the Universal Declaration of Human Rights (DUDH), the Federal Constitution of 1988 (CF) and Law No. 8080 of 1990, health is a fundamental right for all and must be guaranteed by the State. In order to maintain the security of this individual right, communication is the primordial mechanism, as health care is provided in/through dialogued interaction between patient and servants (doctors, nurses and other health professionals). Deaf people have the legal right to linguistic accessibility through the use of sign language, but due to the lack of investment in language policies aimed at the health area; they have been harmed in their care. Therefore, this research problematizes this field by describing public accessibility policies through cartography of the health field in a city in the interior of the state of São Paulo. We surveyed the actions carried out (or not) in the city studied, regarding the effectiveness of bilingual health (in Brazilian Sign Language and Portuguese) for the deaf, as stated in legal documents. This is a qualitative research based on the theoretical-philosophical proposal of Michel Foucault, with principles of archeogenealogy and deleuze-guattarinean cartography. In this investigative practice, historical archives are used, such as official documents, discursive productions of subjects, in order to seek the production and historical function of these discursivities and how they operate in the practical life of these subjects, affecting the production of subjectivation processes by relations of power and knowledge. We collected data from a survey of legal provisions on institutional websites, in a field diary of this researcher's activities, in a community interpretation of Libras in the sphere of health; in interviews with professionals from the Municipal Health Department and in interviews given by deaf people who use these services. We analyzed data from theoretical-philosophical studies, from the perspective of the philosophy of difference (Michel Foucault, Gilles Deleuze and Félix Guattari) and from authors of Deaf Studies and Sign Language Translation and Interpretation Studies. By pointing out the weaknesses present in health services aimed at deaf people, speakers of Libras, we understand that it will be possible to help new reflections for this field. Thus, we hope that the results of this research will contribute to future studies, as well as to discussions in the health area, in the training and practice of services in this area, developing bilingual health centers, aimed at the deaf population, in order to have the guarantee of access to this fundamental right.
Public policies on bilingual health for the deaf: routes, mishaps and daily life
Keywords: Saúde bilíngue em Libras; Surdos; Biopolítica; Biopoder; Racismo de Estado; Bilingual health in Libras; Deaf; Biopolitics; Biopower; State Racism; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM